Exploring directionality in translation studies - Pavlović, Tanja (ExELL, 2013)
The paper analyzes the elements of directionality in translation and its implication on the quality of translation from the second language into the first (L1 translation) and translation from the first language into the second (L2 translation). The traditional view of directionality in translation studies completely neglects L2 translation, often qualifying it as impossible, inappropriate, etc. However, various studies conducted in European countries indicate that this type of translation is not only possible but highly needed, especially in the countries where less disseminated languages or languages of limited diffusion (LLDs) are spoken. The paper will first present the traditional standpoints and then provide the opposite views followed by the analysis of both types of translation. The results of this study show that both L1 and L2 translations are possible and that both directions include certain difficulties.